2021
DOI: 10.1167/iovs.62.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Targeting of the Ammonia-Sensitive Uncoupler SLC4A11 by the Chaperone-Mediated Carrier Pathway in Corneal Endothelium

Abstract: Purpose SLC4A11, an electrogenic H + transporter, is found in the plasma membrane and mitochondria of corneal endothelium. However, the underlying mechanism of SLC4A11 targeting to mitochondria is unknown. Methods The presence of mitochondrial targeting sequences was examined using in silico mitochondrial proteomic analyses. Thiol crosslinked peptide binding to SLC4A11 was screened by untargeted liquid chromatography/tandem mass spectrometry (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Parents of CHED children who are heterozygous for SLC4A11 mutations also appear to be at risk of developing FECD [ 34 ]. No other human disorders have been definitively associated with SLC4A11; however, there are some reports from animal models that suggest kidney involvement (polyuria) [ 32 , 35 , 36 , 37 ] and submandibular gland dysfunction [ 38 ], which is consistent with the strong expression of SLC4A11 in these tissues.…”
Section: Disease Associationsmentioning
confidence: 89%
See 4 more Smart Citations
“…Parents of CHED children who are heterozygous for SLC4A11 mutations also appear to be at risk of developing FECD [ 34 ]. No other human disorders have been definitively associated with SLC4A11; however, there are some reports from animal models that suggest kidney involvement (polyuria) [ 32 , 35 , 36 , 37 ] and submandibular gland dysfunction [ 38 ], which is consistent with the strong expression of SLC4A11 in these tissues.…”
Section: Disease Associationsmentioning
confidence: 89%
“…Inhibiting the HSP90 or HSC70 chaperone pathways in transfected cells and WT MCEC in turn inhibited the delivery of SLC4A11 to mitochondria, consistent with reduced glutamine dependent OCR, reduced ammonia production, and increased mitochondrial superoxide production. Moreover, Choi et al [ 37 ] showed reduced OCR in mitochondria isolated from SLC4A11 KO MCEC and mouse kidney following inhibition of chaperone activity, confirming that the metabolic alterations seen in SLC4A11 deficient cells are not due to non-mitochondrial effects. Heat shock protein expression is typically increased by oxidative stress.…”
Section: Trafficking To Mitochondriamentioning
confidence: 91%
See 3 more Smart Citations